Investigation on tribological behaviors of biodegradable pure Zn and Zn-X (Li, Cu, Ge) binary alloys - Huafang Li (Springer, 2021)
Abstract As a potential biodegradable implant material, zinc (Zn) alloys have attracted increasing attention due to their good biocompatibility and moderate degradation rate. Zn and its alloys are expected to become candidate materials for medical devices. The metals implanted in the human body will inevitably undergo friction in the human body before it is completely degraded. Friction and wear are essential factors which may cause medical devices’ service failure. However, there are still few studies on the friction and wear properties of biodegradable Zn-based alloys in the human body, and most studies just focus on the mechanical properties, degradation properties and biocompatibility of the alloys. Thus, it is crucial to study the friction and wear properties of Zn and its alloys. In the present work, we investigated the tribological properties of biodegradable pure Zn and Zn-X (Li, Cu, Ge) alloys. Our study found that under simulated body fluid and dry friction conditions, the addition of alloying elements Li and Cu can improve the friction properties of Zn. Among the four metals, Zn-0.5Li alloy has the lowest friction coefficient and the best wear resistance. Hank’s solution has lubricating and corrosive effects. That is to say, when the alloy is rubbed in Hank’s solution, it can not only be protected by the lubrication of the solution, but also tribocorrosion will occur as well.